2021
DOI: 10.1007/978-3-030-89029-2_2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Animations in the Perception of a Simulated Crowd

Abstract: Simulating virtual crowds is an important challenge in many areas such as games and virtual reality applications. A lot of effort has been dedicated to improving pathfinding, collision avoidance, or decision making, to achieve more realistic human-like behavior. However, crowd simulation will be far from appearing realistic as long as virtual humans are limited to walking animations. Including animation variety could greatly enhance the plausibility of the populated environment. In this paper, we evaluated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The area of group perception has grown in recent years. Group perception is essential for learning about group patterns [McDonnell et al 2008, Molina et al 2021, Musse et al 2021]. However, these results did not take into account the effect of UV and the use of VR in these scenarios, which is what we want to explore in our work.…”
Section: Related Workmentioning
confidence: 97%
“…The area of group perception has grown in recent years. Group perception is essential for learning about group patterns [McDonnell et al 2008, Molina et al 2021, Musse et al 2021]. However, these results did not take into account the effect of UV and the use of VR in these scenarios, which is what we want to explore in our work.…”
Section: Related Workmentioning
confidence: 97%
“…Their results showed that adding simple secondary shoulder motion to the VHs collision avoidance behaviour increases the perceived naturalness of the situation while hiding the perceived residual collisions. Local body animation characteristics have also been considered by Molina et al [MRP21]. Authors showed that adding animation variety on top of the simulated locomotor trajectory not only increases the overall perceived realism of the simulated crowd but also the perceived realism of the locomotion trajectory and the animation.…”
Section: Taxonomy Of Animation Features Influencing Virtual Human Rea...mentioning
confidence: 99%
“…The results obtained showed that avatars with a human appearance and varied animations were perceived as more realistic than any other combination for the group of participants that rated the videos. This work has been published in the Computer Graphics International 2021 (CGI) (Molina et al, 2021).…”
Section: Perception Of Realismmentioning
confidence: 99%